2008
DOI: 10.1097/mlg.0b013e3181864acf
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Effect of OK‐432 (Picibanil) Sclerotherapy for Benign Neck Cysts

Abstract: OK-432 sclerotherapy is a safe and effective primary alternative to surgery in patients with benign neck cysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 15 publications
0
52
0
2
Order By: Relevance
“…[36][37][38]55,57,[81][82][83] Fukase et al 36 observed that patients who had clinical evidence of a strong local inflammatory reaction showed an obvious curative effect, which indicates that there is an increase of the chronic inflammatory reaction present in the ranula in which macrophages break down extravasated mucus, which would increase the removal of extravasated mucus. Fukase et al 36 also observed that the viscosity of the fluid in the ranula increased, and they suggested that fibrinous exudate produced by the inflammation sealed the leak.…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38]55,57,[81][82][83] Fukase et al 36 observed that patients who had clinical evidence of a strong local inflammatory reaction showed an obvious curative effect, which indicates that there is an increase of the chronic inflammatory reaction present in the ranula in which macrophages break down extravasated mucus, which would increase the removal of extravasated mucus. Fukase et al 36 also observed that the viscosity of the fluid in the ranula increased, and they suggested that fibrinous exudate produced by the inflammation sealed the leak.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al 18 reported that transient mild local pain and lowgrade fever were observed, but there were no significant treatment-related complications. In their study, some patients complained of mild pain and discomfort related to needle puncture; however, there were no significant complications.…”
Section: Discussionmentioning
confidence: 99%
“…13,14,18 Kim et al 18 described OK-432 therapy for TGDC, and the success rate was found to be 45.5% (5/11) without significant complications. Previous reports of EA for TGDC indicated that successful treatment was achieved in 60% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…용적 문제 등의 합병증 발생률도 높아 [1,7] 최근에는 특히 두 경부에 위치한 크기가 5 cm 미만의 대낭성 병변의 경우 OK-432를 이용한 경화요법이 최선의 치료법으로 여겨지며 제한 된 경우에 있어서 수술적 치료가 행하여진다. 반복된 경화요 법 이후에 수술을 시행하는 경우에는 주변 조직과의 유착 및 출혈로 수술 중 어려움을 겪을 수 있다 [8].…”
Section: Journal Of Korean Association Of Pediatric Surgeonsunclassified